Application of Ta'zir Punishment for Perpetrators of Corruption in the Perspective of Islamic Criminal Law - Zaki Azmi Daffa; Alfiko Gio Pratama; Abdurrasyid Karim; Rayhan Nandini Telaumbanua; Suci Hidayati Malau (ISNU Nine-Star Multidisciplinary Journal, 2025)
Corruption is an extraordinary crime that causes great losses to state finances, damages social order, and erodes public trust. In Indonesia's positive law, corruption has been regulated in detail through various laws. However, a normative approach alone is not enough to provide a deterrent effect on the perpetrators. Therefore, Islamic law as a legal system rich in moral values and substantive justice offers an alternative approach through the concept of ta'zir punishment. This study aims to examine how the application of ta'zir punishment can be relevant and effective against corrupt perpetrators in the perspective of Islamic criminal law. The method used is normative legal research with a conceptual and historical approach. Data was obtained through literature studies on primary sources of Islamic law such as the Qur'an, hadith, and fiqh books, and also through analysis of positive legal regulations in Indonesia. The results of the study show that corruption in Islamic law can be categorized as jarimah ta'zir, so that the form and degree of punishment can be determined by the competent authorities. The punishment of ta'zir is flexible and can be in the form of imprisonment, fines, restitution of property, and social or administrative punishment. The principles of justice and benefit contained in ta'zir are considered to be able to provide a deterrent effect while encouraging moral reform of the perpetrators. This concept is relevant to be integrated into the national legal system in terms of values and ethics.